A multi-perspective factorial hypothetical simulation model for cutting the carbon emission intensity of China. (1st December 2020) - He, Chengyu; Huang, Guohe; Liu, Lirong; Li, Yongping; Zheng, Boyue; Guan, Yuru
Abstract: Climate change is a huge threat to our globe. As the largest CO2 emitter and the biggest developing country in the world, China has pledged to cut its national carbon emission intensity (NCEI). The objective of this study is to develop a multi-perspective factorial hypothetical simulation model to facilitate the policy development for robust NCEI reduction. Based on multi-regional input-output model and hypothetical extraction method, the individual- and the system-based effects of 900 sectors on NCEI are investigated. Then, targeted countermeasures against key sectors are developed. After that, the effects and the complex interactions of the countermeasures on the system robustness and the system sustainability are examined by factorial analysis. The results reveal that it is feasible to cut NCEI of China through the proper adjustments of a few sectors, while some of them may at the cost of the system health. For example, controlling the production-based CO2 emission of Electricity and hot water production and supply in Shandong and shrinking the production scale of Metallurgy in Hebei could efficiently cut China's NCEI. However, the two countermeasures would deteriorate the system health through their main effects and interaction. These findings can provide new information for achieving China's NCEI goal. Highlights: A multi-perspective factorial hypothetical simulation model is developed. A study of China is conducted on National Carbon Emission Intensity (NCEI). Individual- and system-based effects of sectors on NCEI are examined. Effects and interactions of policies on the system performances are investigated.